Pengaruh Rutinitas Membaca Al–Qur’an Sebelum Belajar Terhadap Prestasi Belajar Siswa di Madrasah Diniyah Takmiliyah Ula - Rafika, Elsa; Akil; Acep Nurlaeli (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The Qur'an is a holy book that is used as a guide to life for Muslims in the world. Reading the Koran repeatedly not only improves brain function, but can soothe the heart and soul, making the reader calm. This research was conducted in class V of Madrasah Diniyah Takmiliyah Ula with the aim of finding out the influence of the routine of reading the Koran before studying on students' learning achievement in class V of Madrasah Diniyah Takmiliyah Ula. The activity of reading the Koran before the lesson starts, is carried out with the guidance and supervision of the teacher who teaches at the start of the lesson, and takes approximately 15 – 20 minutes. With the habit of frequently reading the Qur'an, students will become good human beings, can provide calm and peace, get the protection and grace of Allah, get high degrees, eliminate all doubts and get forgiveness of sins from Allah SWT and make it easier to gain knowledge. in everyday learning.The type of research used is quantitative research. The sample in this research was class V of Madrasah Diniyah Takmiliyah Ula, totaling 29 students. The results of this study show that there is a significant influence between the variable of the routine of reading the Al-Qur'an before studying on Islamic Religious Education learning achievement in cognitive, affective and psychomotor aspects. Based on the research results, it can be concluded that the average learning ability or achievement of students in class V of Madrasah Diniyah Takmiliyah Ula is closely related to the routine of reading the Al-Qur'an before studying.